Modelling of Green function in a rectangular room based upon the geometrical-filtration model - Marczuk, R.; Majkut, L. (Archives of Acoustics, 2006)
Significant problem in room acoustic is evaluating an acoustic quality of projected and modernized rooms. Estimation of room impulse response giving posibility to evaluate the subjective and objective room acoustic properties and hence to run the room simulation tests (the sound sources configuration, the room planning) in order to reach optimal solutions, which meet the given criterion. To this end it is necessary to work out an impulse response calculating algorithm for a digital room model.The Green's function is the solution of wave equation then give consideration to source and receiver positions. For inhomogenous wave equation with function $δ(x-y)δ(t-τ) as excitation, Green's function corresponds to the impulse response of linear system described by this equation.This paper presents a Green function (impulse response) approximation method based on combined room acoustics model. Sound propagation paths are calculated using geometrical acoustics model (image sources method) while events like reflection from bounding walls, air absorption and delay between events are modeled as digital filters.Results of room impulse response approximation model are compared with analytical solution for rectangular room.